IMPLEMENTASI PRODUK INOVASI TEMPAT PEMBAKARAN SAMPAH â€œPAKAR PALING BERHATIâ€ DI DESA CIHIDEUNG ILIR, BOGOR - Juliano, Kurnia Ronaldo; Irwan, Mutiara Selvayanti; Alfareza, Fikri; Putri, Zahra Assyifa; Ariyanti, Novie; Fitriyani, Amanda; Fachri, Muhammad Ryan; Ruswendra, Muhammad; Syihab, Faizah (Institut Teknologi dan Bisnis Swadharma, 2024)
The environment plays a vital role in sustaining life on Earth, particularly for humans. Maintaining a clean and healthy environment is crucial, as it significantly impacts the well-being of all living beings. This study explores the challenges of improper waste disposal in Desa Cihideung Ilir, located in the Ciampea district of Bogor Regency, West Java, Indonesia. The inadequate waste management in this area has led to pollution, health risks, and a negative impact on the community's quality of life. The research involves the development of an innovative solution known as